The Influence of Organization-Based Self-Esteem and Employee Engagement toward Organizational Citizenship Behavior - Herrysono, Jevon Jeremy Nicholas; Franksiska, Rosaly (Jurnal Bisnis dan Manajemen, 2022)
This study aimed to investigate the effect of Organization based Self Esteem (OBSE) and Employee Engagement on Organizational Citizen Behavior (OCB) of foreign-owned bank in Cirebon. To obtain data, a sample of 103 employees was taken at several banks with foreign ownership status in Cirebon using an accidental sampling technique. The analytical tool used is multiple regression analysis. The results showed that both OBSE and Employee Engagement had a positive and significant effect on the OCB of employees at several banks with foreign ownership status in Cirebon.